Future vision of the Peruvian coal - Luyo Quiroz, Antonio (2012)
In our country for decades has made mention of our coal, has even invested large sums of money trying to study this resource, access, exploitation and industrialization. Entities as INGEMMET, Minero Peru and SIDERPERÚ, invested in projects such as "Coal Mining", "Transport of solids by pipeline," "Exploitation of coal Oyón" and "evaluation for the extraction of coal from Santa." Attempts have been made to investigate its use and how you will toward the centers of consumption is projected to do power plants in production areas to prevent transfer, trying to design and transform existing machines directing this production of coal due to the domestic market there are only machines for metal mining, but what results have you had? In this article we want to answer this question and comment on the future of this resource. In two state research institutions and Minero Peru INGEMMET and SIDERPERÚ particularly engaged, was counted as studies based on the work done by Julio Escudero Ratto, who studied the carbon Peru, deeply studied coal from Santa and coordinated the work done by the German KFW Fund by dividing INGEMMET Mining, obtaining some results which we will explain in this article.